Pengaruh Model Experiential Learning terhadap Kemampuan Menulis Puisi Siswa Kelas VIII SMP Negeri 36 Medan - Indah Rosa Damanik; Safinatul Hasanah Harahap (Lembaga Yasin AlSys, 2026)
The low level of students’ poetry writing ability, caused by limited ideas, a lack of direct experience, and the use of ineffective instructional models, highlights the need for innovative learning approaches in Indonesian language teaching. Poetry writing instruction that tends to be overly theoretical makes it difficult for students to express their experiences and feelings in literary form. This study aimed to determine the effect of implementing the experiential learning model on the poetry writing ability of eighth-grade students at SMP Negeri 36 Medan. A quantitative approach with a quasi-experimental method and a one-group pretest–posttest design was employed on a sample of 30 eighth-grade students. Data were collected through poetry writing tests administered before and after the treatment, and were analyzed using normality tests, homogeneity tests, and t-tests to examine differences in students’ poetry writing ability before and after the implementation of the instructional model. The results showed an improvement in poetry writing ability following the application of the experiential learning model, as evidenced by a t-calculated value greater than the t-table value at the 0.05 significance level, leading to the acceptance of the alternative hypothesis. The improvement was evident in aspects of diction, imagery, clarity of content, and use of figurative language. The study concludes that the experiential learning model has a significant effect on students’ poetry writing ability and indicates that experience-based learning is effective as an alternative instructional model for teaching poetry writing to enhance students’ creativity and expressive skills.